Subclavian carotid transposition: A single-center experience - Hemachandren Munuswamy; Duvuru Ram; Sreevathsa Prasad; Suresh Kumar Rajan; Durgaprasad Rath; Bathal Vedagiri Saichandran (Indian Journal of Vascular and Endovascular Surgery, 2019)
Objective: Subclavian carotid transposition (SCT) is generally performed for stenoocclusive disease of the proximal subclavian artery. This study was undertaken to analyze the results of SCT at our center and also highlight the usefulness of this procedure in varied pathologies involving the proximal subclavian artery. Patients and Methods: This retrospective study included 16 consecutive patients from 2011 to 2016 who presented to our department. The study was carried following approval by the Institute Research Committee and the Institute Ethics Committee. The data were collected from the departmental database, and the patients were followed up prospectively and the data were analyzed. Results: The mean age of the patients at presentation was 46.6 years with standard deviation of 11.48. Eleven patients (78%) had total occlusion of the proximal subclavian artery. About 81% of the patients had left-sided SCT. The etiology for SCT was varied with ten patients (62.5%) having proximal subclavian artery occlusion with chronic upper-limb ischemia, three patients (18.75%) with acute subclavian artery occlusion, one patient with bilateral cervical ribs, one patient with dysphagia lusoria with aberrant right subclavian artery (ARSA), and one patient with right common carotid aneurysm. The mean follow-up duration was 64 months. The patency rate was 100% in the study population. There were no immediate occlusions or stenosis noted in our series. Conclusion: SCT is a safe, effective, and durable procedure with long-term patency rates with less morbidity and reintervention rates. It can be safely done for both acute and chronic subclavian artery occlusions and various other conditions too such as dysphagia lusoria due to ARSA and cervical rib with subclavian artery occlusion. Hence, a vascular surgeon should master the art of doing SCT for its good results and for its being effective for varied pathologies.